2000
DOI: 10.1007/bf03165921
|View full text |Cite
|
Sign up to set email alerts
|

A novel system for studies of dc discharge in cylindrical magnetron

Abstract: In a cylindrical magnetron, the electric field is applied in the radial direction and the magnetic field in the axial direction. In this paper, we present a description of a novel construction of cylindrical magnetron developed in the University of Greifswald, FRG. The system has been designed for experimental and computer-modelling studies of the DC discharge in crossed electric and magnetic fields in cylindrical geometry. In order to approach conditions close to an infinitely long system, and hence, to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This difference has been attributed to the end effects that are not taken into account in the one-dimensional model. In order to minimise the end effects, a novel experimental system has been constructed where the length/radius ratio of the discharge chamber is much higher compared to the present system [9].…”
Section: Resultsmentioning
confidence: 99%
“…This difference has been attributed to the end effects that are not taken into account in the one-dimensional model. In order to minimise the end effects, a novel experimental system has been constructed where the length/radius ratio of the discharge chamber is much higher compared to the present system [9].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous experimental studies we already reported the presence of fluctuations of the plasma potential in cylindrical magnetron system [4,5]. Fluctuations manifested themselves as an unwanted noise added to the Langmuir probe floating potential when measuring with the floating probe and in the increased noise of the measured current when measuring the V-A probe characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…The plasma in axial direction becomes inhomogeneous and with that also the axial components of the radial current densities to the cathode. In the last periods of the SFB 198, therefore a magnetron of a length of 30 cm with 6 magnetic coils and 5 ports for probe measurements in radial direction was used [5], [10]. Half of the cylindrical cathode was subdivided in 14 segments, which were electrically isolated of each other.…”
Section: Introductionmentioning
confidence: 99%